Population structure of the invasive forest pathogen Hymenoscyphus pseudoalbidus. Issue 12 (12th June 2014) - Gross, Andrin; Hosoya, Tsuyoshi; Queloz, Valentin
Abstract Understanding the genetic diversity and structure of invasive pathogens in source and in introduced areas is crucial to the revelation of hidden biological features of an organism, to the reconstruction of the course of invasions and to the establishment of effective control measures. Hymenoscyphus pseudoalbidus (anamorph: Chalara fraxinea) is an invasive and highly destructive fungal pathogen found on common ash Fraxinus excelsior in Europe and is native to East Asia. To gain insights into its dispersal mechanisms and history of invasion, we used microsatellite markers and characterized the genetic structure and diversity of H. pseudoalbidus populations at three spatial levels: (i) between Europe and Japan, (ii) in Europe and (iii) at the epidemic's front in Switzerland. Phylogenetic and network analysis demonstrated that individuals from both regions are conspecific. However, populations from Japan harboured a higher genetic diversity and were genetically differentiated from European ones. No evident population structure was found among the 1208 European strains using Bayesian and multivariate clustering analysis. Only the distribution of genetic diversity in space, pairwise population differentiation (GST) and the spatial analysis of principal components revealed a faint geographical pattern around Europe. A significant allele deficiency in most European populations pointed to a recent genetic bottleneck, whereas no pattern of isolation by distance was found. Our data suggest that H. pseudoalbidus was introduced just once by at least two individuals. The potential source region of H. pseudoalbidus is vast, and further investigations are required for a more accurate localization of the source population.